Reply to comment on Improving Poor Man's Kramers-Kronig analysis and Kramers-Kronig constrained variational analysis - Mayerhoefer, Thomas G.; Popp, Juergen (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2021)
We reply to a comment made in [E. Rousseau, N. Izard, J.-L. Bantignies, D. Felbacq, Comment on the paper ”Improving Poor Man's Kramers-Kronig analysis and Kramers-Kronig constrained variational analysis”, Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy, (2021) 119849].
CRIS-Team Scopus Importer:2023-04-20